Analysis of Student Response to the Use of Biochemistry e-Module on Carbohydrate Materials in Enhanching Learning Independence - Mairisiska, Titin; Ramadani, Ramadani; Qadariah, Nosi (Universitas Pendidikan Mandalika, 2025)
This study aims to analyze student responses to the use of a biochemistry e-module on carbohydrate material and its impact on learning independence. This quantitative descriptive research involved 40 students from the Biology and Chemistry study programs who had used the e-module. Data were collected through a questionnaire covering five indicators: ease of use, effectiveness of material delivery, level of interactivity, learning independence, and general response. The results showed that for the ease of use indicator, the carbohydrate e-module received an average response of